170 Hispanic Ethnicity May Be Associated with Short Sleep Duration and Elevated Sleep Distress in U.S. Air Force Trainees. (3rd May 2021) - Burns, Rosemary Estevez; Wang, Xin Qun; Patience, Marc; Ellis, Jordan; Talcott, Wayne; Hryshko-Mullen, Ann; Star, John Blue; Copeland, Carol
Abstract: Introduction: Sleep research among Hispanic populations is limited. Hispanics may be at higher risk of poor sleep when compared to other race/ethnicities. Non-white and other socioeconomically disadvantaged populations have higher rates of chronic health conditions. Epidemiological studies have substantiated the correlation between short sleep and a variety of negative health outcomes. Sleep is foundational to overall good health and functioning, impacting academic and physical performance in technical training, and crucial for an airmen's adjustment to the rigor of a military career. Authors explored the role of race/ethnicity on perceived sleep health (e.g., sleep duration and sleep distress) among airmen attending technical school. Methods: Sleep health survey was administered to two groups of Airmen at an Air Force technical training: In-processing: Airmen who just arrived to begin technical training, (n=187), Age: M= 20.83 (SD 3.26), 82.55% Male; upon completion of training, i.e., Out-processing: Airmen about to complete technical training, (n=302), Age M = 20.7 (SD 3.09), 85.81% Male. To account for correlations between Airmen from the same squadron, a covariates-adjusted generalized mixed-effects model was used. Associations between race/ethnicity and short sleep duration (≤6 hours), and between race/ethnicity and sleep pattern distress—among shorter sleepers as a sub-group—were examined. Racial/Ethnic frequency among short sleepers (n=135): 19.3 % Hispanic, 13.3% NH-Black, 55.6% NH-White, 6.6% NH-Multiracial, and 5.2% NH-Other. Results: Among Hispanic Airmen, the out-processing group was 2.25 times as likely as the in-processing group to be short sleepers on weekdays (95% CI: 1.15 to 4.38, p=0.017). Among short sleepers in the out-processing group, Hispanic Airmen were significantly more worried/distressed about their sleep pattern than Black and White Airmen (OR=2.29, 95% CI: 1.18 to 4.42, p=0.014 and OR=2.29, 95% CI: 1.10 to 4.76, p=0.026, respectively). Conclusion: Short sleep duration is a significant problem in the military and results suggest that race/ethnicity-related contextual factors may point to at risk subgroups. Others have considered the influence of perceived prejudice, access to social capital, cultural barriers to academic success, and potential sensitivity to somatic discomfort on sleep complaints. Future directions involve repeating this assessment with another cohort of technical training Airmen to see if findings replicate. Support (if any): none